2022
DOI: 10.1186/s12885-022-09754-3
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative PDW levels predict pulmonary metastasis in patients with hepatocellular carcinoma

Abstract: Background In hepatocellular carcinoma (HCC), pulmonary metastasis (PM) after hepatectomy is associated with poor clinical outcomes. The crucial phases of tumour cell proliferation, angiogenesis, and metastasis all entail platelet activation. In HCC, platelet distribution width (PDW) suggests platelet size changes and predicts a worse prognosis. The aim of this study was to assess the association between PDW and PMs in HCC patients receiving hepatectomy. Material/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Generally, the ultrasound examination and serum alpha-fetoprotein (AFP) levels are widely utilized for the early screening of high-risk populations, and the suspected patients subsequently obtain a clinical or definitive diagnosis via the CT/MRI enhanced scanning or liver biopsy. In recent years, several commonly used blood routine and biochemistry indexes have also attracted much attention from researchers in addition to the classic serum oncology biomarkers, which have the potential to serve as prospective indicators for prognosis assessment and risk stratification of patients with HCC independently or synergistically [ 27 29 ], and platelet is one of the representatives [ 11 , 30 32 ]. Studies have demonstrated that abnormal platelet counts (including thrombocytopenia and thrombocytosis) are closely related to the poor OS of patients with HCC [ 30 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the ultrasound examination and serum alpha-fetoprotein (AFP) levels are widely utilized for the early screening of high-risk populations, and the suspected patients subsequently obtain a clinical or definitive diagnosis via the CT/MRI enhanced scanning or liver biopsy. In recent years, several commonly used blood routine and biochemistry indexes have also attracted much attention from researchers in addition to the classic serum oncology biomarkers, which have the potential to serve as prospective indicators for prognosis assessment and risk stratification of patients with HCC independently or synergistically [ 27 29 ], and platelet is one of the representatives [ 11 , 30 32 ]. Studies have demonstrated that abnormal platelet counts (including thrombocytopenia and thrombocytosis) are closely related to the poor OS of patients with HCC [ 30 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The liver is a substantial organ with a dual blood supply system, and this anatomical characteristic also makes it necessary to explore the potential function of platelets in liver diseases, especially in HCC. In current studies, clinical explorations about platelets in HCC mainly concentrate on the significance of the variation of platelet counts or morphology as well as the platelet-related ratio in prognostic prediction [ 9 11 ]. While from the perspective of clinical findings combined with molecular changes, whether there are corresponding abnormal changes in platelet-related genes in the development of HCC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that abnormal platelet counts (including thrombocytopenia and thrombocytosis) are closely related to the poor OS of patients with HCC (26, 29). Additionally, aberrant changes in morphology or functional status of platelet have also been discovered to be connected with tumor metastasis and patients' adverse outcomes (11,27). Actually, the intimate connection between platelets and tumor progression has been widely recognized, numerous fundamental research has proved that platelets take an essential part in mediating cancer proliferation, angiogenesis, invasion and metastasis, as well as immune escape (4).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the ultrasound examination and serum alpha-fetoprotein (AFP) levels are widely utilized for the early screening of high-risk populations, and the suspected patients subsequently obtain a clinical or de nitive diagnosis via the CT/MRI enhanced scanning or liver biopsy. In recent years, several commonly used blood routine and biochemistry indexes have also attracted much attention from researchers in addition to the classic serum oncology biomarkers, which have the potential to serve as prospective indicators for prognosis assessment and risk strati cation of patients with HCC independently or synergistically (23)(24)(25), and platelet is one of the representatives (11,(26)(27)(28). Studies have demonstrated that abnormal platelet counts (including thrombocytopenia and thrombocytosis) are closely related to the poor OS of patients with HCC (26, 29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation